2017
DOI: 10.5455/ijhrs.0000000126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lower limb Spasticity on Gait in People with Multiple Sclerosis; Review

Abstract: Objective: The aim of this paper is to review literature systematically and quantify the effects of leg spasticity on gait parameters in PwMS. Methods and Materials:This study is a systematic review and meta-analysis of observational studies. Articles were included if they met the following inclusion criteria: They were original, observational studies, participants were PwMS, study the effects of leg spasticity on gait in MS patients compared with MS patients without spasticity. The included articles were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The prevalence of spasticity ranges from 52% to 84% in the MS population (5,6). Although spasticity occurs in the upper limbs, lower limb spasticity is predominant in MS. Several studies have revealed that lower limb spasticity related to walking, postural control, and severe disability profoundly affects the quality of life in persons with multiple sclerosis (pwMS) (7,8). Furthermore, spasticity affects daily life activities in those with MS (9).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of spasticity ranges from 52% to 84% in the MS population (5,6). Although spasticity occurs in the upper limbs, lower limb spasticity is predominant in MS. Several studies have revealed that lower limb spasticity related to walking, postural control, and severe disability profoundly affects the quality of life in persons with multiple sclerosis (pwMS) (7,8). Furthermore, spasticity affects daily life activities in those with MS (9).…”
Section: Introductionmentioning
confidence: 99%